The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/pen.25123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different size‐modified expandable graphite and ammonium polyphosphate on the flame retardancy, thermal stability, physical, and mechanical properties of rigid polyurethane foam

Abstract: In this study, three different sizes of tripolyphosphate‐modified expandable graphite (EGp) are prepared and incorporated into rigid polyurethane foam (RPUF) in order to obtain a flame retardant material with low density, good mechanical properties, and hydrophobicity. The influence of particle size on material combustibility, thermal stability, compression strength, pore cell structure, diathermancy, and hydrophobic property is investigated. Synergistic effect between the EGp and ammonium polyphosphate (APP I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 56 publications
2
22
2
Order By: Relevance
“…The T onset of VER/APP is 336°C, which decreases 15°C in contrast to the T onset of the pure VER. This reduction is caused by the degradation of APP, which can produce polyphosphoric acid that can react with hydroxyl of VER, which is conducive to formation of protective char layer , so the char residues of VER/APP is improve obviously until 600°C. However, with increase of temperature, the oxidation of the char layer happened and only 3.7% char residues were remained at 800°C, which indicate that the char layer of VER/APP composite formed during the thermal decomposition showed a poor resistance to thermal oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The T onset of VER/APP is 336°C, which decreases 15°C in contrast to the T onset of the pure VER. This reduction is caused by the degradation of APP, which can produce polyphosphoric acid that can react with hydroxyl of VER, which is conducive to formation of protective char layer , so the char residues of VER/APP is improve obviously until 600°C. However, with increase of temperature, the oxidation of the char layer happened and only 3.7% char residues were remained at 800°C, which indicate that the char layer of VER/APP composite formed during the thermal decomposition showed a poor resistance to thermal oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 36 ] showed the addition of 30 parts per hundred of polyol by weight of graphite with an average particle size of 960, 340, and 70 µm, resulting in semirigid polyurethane foams with flammability class V0, V1, and HB75. A better flame-retardant effect for foams with larger grain size graphite results from the formation of a greater amount of char residue [ 32 , 37 ]. Moreover, the addition of approximately 30 parts per 100 of polyols by weight ensures that the oxygen index of rigid polyurethane foams is 25% [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pang et al have incorporated three different sizes of tripolyphosphate-modified expandable graphite (EGp) into RPUF. As the size of EGp increases, RPUFs showed an increased LOI (limiting oxygen index) and a decreased heat release [ 32 ]. Chen et al introduced 15 wt.% EG into RPUF and found that the PHRR and total heat release (THR) were decreased by 36.2% and 22.0%, respectively [ 33 ].…”
Section: Introductionmentioning
confidence: 99%